Question Number 128005 by mnjuly1970 last updated on 03/Jan/21 | ||
$$\:\:\:\:\:\:\:\:\:\:\:\:\:....{nice}\:\:\:{calculus}... \\ $$ $$\:\:{if}\:\:{b}>{a}>\mathrm{0}\:{then}\:{prove}\::: \\ $$ $$\:\:\:\:\:\:\:\:\frac{{a}+{b}}{\mathrm{2}}>\:\frac{{b}−{a}}{{ln}\left({b}\right)−{ln}\left({a}\right)}\:>\:\sqrt{{ab}}\: \\ $$ $$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:............................ \\ $$ | ||
Answered by mindispower last updated on 06/Jan/21 | ||
$$\Leftrightarrow\frac{\frac{{b}}{{a}}+\mathrm{1}}{\mathrm{2}}>\frac{\frac{{b}}{{a}}−\mathrm{1}}{{ln}\left(\frac{{b}}{{a}}\right)}>\sqrt{\frac{{b}}{{a}}} \\ $$ $$\frac{{b}}{{a}}={x},{x}>\mathrm{1} \\ $$ $$\Rightarrow\frac{{x}+\mathrm{1}}{\mathrm{2}}=\frac{{x}−\mathrm{1}}{{ln}\left({x}\right)}>\sqrt{{x}} \\ $$ $$\Leftrightarrow{ln}\left({x}\right)>\frac{\mathrm{2}\left({x}−\mathrm{1}\right)}{{x}+\mathrm{1}}..\mathrm{1} \\ $$ $$\&{ln}\left({x}\right)<\sqrt{{x}}−\frac{\mathrm{1}}{\:\sqrt{{x}}},..\mathrm{2} \\ $$ $$\mathrm{1}\Leftrightarrow{f}\left({x}\right)={ln}\left({x}\right)−\mathrm{2}+\frac{\mathrm{4}}{{x}+\mathrm{1}}>\mathrm{0} \\ $$ $${f}'\left({x}\right)=\frac{\mathrm{1}}{{x}}−\frac{\mathrm{4}}{\left({x}+\mathrm{1}\right)^{\mathrm{2}} }=\frac{\left({x}−\mathrm{1}\right)^{\mathrm{2}} }{{x}\left({x}+\mathrm{1}\right)^{\mathrm{2}} }>\mathrm{0} \\ $$ $${f}\left({x}\right)>{f}\left(\mathrm{1}\right),\forall{x}>\mathrm{1} \\ $$ $${f}\left(\mathrm{1}\right)={ln}\left(\mathrm{1}\right)−\mathrm{2}+\frac{\mathrm{4}}{\mathrm{2}}=\mathrm{0} \\ $$ $$\Rightarrow\mathrm{1}..{true} \\ $$ $$\mathrm{2}\Leftrightarrow{g}\left({x}\right),\sqrt{{x}}−\frac{\mathrm{1}}{\:\sqrt{{x}}}−{ln}\left({x}\right)>\mathrm{0} \\ $$ $${g}'\left({x}\right)=\frac{\mathrm{1}}{\mathrm{2}\sqrt{{x}}}+\frac{\mathrm{1}}{\mathrm{2}{x}\sqrt{{x}}}−\frac{\mathrm{1}}{{x}}=\frac{{x}+\mathrm{1}−\mathrm{2}\sqrt{{x}}}{\mathrm{2}{x}\sqrt{{x}}}=\frac{\left(\sqrt{{x}}−\mathrm{1}\right)^{\mathrm{2}} }{\mathrm{2}{x}\sqrt{{x}}} \\ $$ $${g}'\left({x}\right)>\mathrm{0},{g}\left(\mathrm{1}\right)=\mathrm{0}\Rightarrow{g}\left({x}\right)>{g}\left(\mathrm{1}\right)=\mathrm{0},\forall{x}>\mathrm{1} \\ $$ $$\mathrm{2}..{true} \\ $$ $$\Rightarrow\frac{{b}−{a}}{\mathrm{2}}>\frac{{b}−{a}}{{ln}\left({b}\right)−{ln}\left({a}\right)}>\sqrt{{ab}},\forall{a},{b}\:\:\:{b}>{a}>\mathrm{0} \\ $$ $$ \\ $$ $$ \\ $$ | ||